2010
DOI: 10.1371/journal.pone.0013802
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Introduction of New Vaccines to Poor Nations: A Comparative Study of the Haemophilus influenzae Type B and Hepatitis B Vaccines

Abstract: BackgroundA major effort to introduce new vaccines into poor nations of the world was initiated in recent years with the help of the GAVI alliance. The first vaccines introduced have been the Haemophilus influenzae type B (Hib) and the hepatitis B (Hep B) vaccines. The introduction of these vaccines during the first phase of GAVI's operations demonstrated considerable variability. We set out to study the factors affecting the introduction of these vaccines. The African Region (AFRO), where new vaccines were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Widely used, vaccination has been effective in preventing HBV infection. 3,4 Hepatitis B immunoglobulin (HBIG) is also important in the management of HBV infection. 5,6 Since vertical transmission is responsible for about 40%-50% of HBV carriers, 5 newborns of mothers who are HBV surface antigen (HBsAg)-positive are generally required to receive HBIG and hepatitis B vaccine within 24 h following delivery and complete the whole regimen of recommended vaccination injections.…”
Section: Introductionmentioning
confidence: 99%
“…Widely used, vaccination has been effective in preventing HBV infection. 3,4 Hepatitis B immunoglobulin (HBIG) is also important in the management of HBV infection. 5,6 Since vertical transmission is responsible for about 40%-50% of HBV carriers, 5 newborns of mothers who are HBV surface antigen (HBsAg)-positive are generally required to receive HBIG and hepatitis B vaccine within 24 h following delivery and complete the whole regimen of recommended vaccination injections.…”
Section: Introductionmentioning
confidence: 99%
“…60,61 Studies have shown that effective governance of health sector organizations can lead to better implementation and uptake of health technologies. 62 Higher regulatory quality and strong public sector financial management, core components of governance, 63 are associated with lower infant mortality rates, 64 reduced corruption , and increased public health spending. 65 However, despite the widely established benefits of governance, LMICs suffer from weak institutions, poor public infrastructure, low legal capacity, 66 and weak accountability mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Glatman-Freedman A et al [84], the authors found that, not only the availability of funding were behind the success of the introduction of the new vaccines into the immunization program of countries in SSA. The authors identified 3 distinct groups of countries from SSA based on the status of NVI or use during the first phase of GAVI's operation (2000)(2001)(2002)(2003)(2004)(2005) (Figure 1).…”
Section: Proactive Planning and Funding Opportunitiesmentioning
confidence: 99%